Perancangan UI/UX Aplikasi Sistem Informasi Pariwisata Kabupaten Jepara Menggunakan Metode Design Thinking - Annisa Rachman; Joko Sutopo (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Jepara Regency is one of the regencies in Central Java that has great tourism potential. However, this potential has not been fully exploited due to a lack of information and promotion. To address this issue, a tourism information system application is needed that can provide complete and accurate information and promotion to tourists. This study uses the design thinking method to design the UI/UX of the tourism information system application of Jepara Regency. This method was chosen because it can involve users in the design process to produce a product that meets the needs and desires of users. The results of the study show that the designed tourism information system application of Jepara Regency has a user-friendly and responsive UI/UX. The application is also equipped with various features that can make it easy for tourists to get information and promotion about tourism in Jepara Regency.